Systematic Review Research Guides and Support Services in Academic Libraries in the US: A Content Analysis of Resources and Services in 2023 - Sterner, Elizabeth A. (Evidence Based Library and Information Practice, 2024)
Objective – The purpose of this research project was to examine the state of library research guides supporting systematic reviews in the United States as well as services offered by the libraries of these academic institutions. This paper highlights the informational background, internal and external educational resources, informational and educational tools, and support services offered throughout the stages of a systematic review.Methods – The methodology centered on a content analysis review of systematic review library research guides currently available in 2023. An incognito search in Google as well as hand searching were used to identify the relevant research guides. Keywords searched included: academic library systematic review research guide.Results – The analysis of 87 systematic review library research guides published in the United States showed that they vary in terms of resources and tools shared, depth of each stage, and support services provided. Results showed higher levels of information and informational tools shared compared to internal and external education and educational tools. Findings included high coverage of the introductory, planning, guidelines and reporting standards, conducting searches, and reference management stages. Support services offered fell into three potential categories: consultation and training; acknowledgement; and collaboration and co-authorship. The most referenced systematic review software tools and resources varied from subscription-based tools (e.g., Covidence and DistillerSR) to open access tools (e.g., Rayyan and abstrackr).Conclusion – A systematic review library research guide is not the type of research guide that you can create and forget about. Librarians should consider the resources, whether educational or informational, and the depth of coverage when developing or updating systematic review research guides or support services. Maintaining a systematic review research guide and support service requires continual training and maintaining familiarity with all resources and tools linked in the research guide.